2002
DOI: 10.1001/archpsyc.59.3.225
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Educational, and Social Role Outcomes of Adolescents With Depression

Abstract: Young people having early depression were at increased risk of later adverse psychosocial outcomes. There was a direct linkage in which early depression was associated with increased risk of later major depression and anxiety disorders. Linkages between early depression and other outcomes appeared to reflect the effects of confounding factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
634
6
18

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 892 publications
(705 citation statements)
references
References 36 publications
30
634
6
18
Order By: Relevance
“…First, disorders that involve externalizing behavior are more consistently associated with termination of schooling across the four milestones than are disorders that involve internalizing behaviors. Neither major depression nor generalized anxiety disorder were associated with subsequent termination of schooling at any of the milestones examined, consistent with the findings of several longitudinal studies (Fergusson et al, 2002;Johnson et al, 1999;Miech et al, 1999). Second, the association of mental disorders with termination of schooling is more consistent across disorders with respect to high school than with respect to any of the other milestones examined.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…First, disorders that involve externalizing behavior are more consistently associated with termination of schooling across the four milestones than are disorders that involve internalizing behaviors. Neither major depression nor generalized anxiety disorder were associated with subsequent termination of schooling at any of the milestones examined, consistent with the findings of several longitudinal studies (Fergusson et al, 2002;Johnson et al, 1999;Miech et al, 1999). Second, the association of mental disorders with termination of schooling is more consistent across disorders with respect to high school than with respect to any of the other milestones examined.…”
Section: Discussionsupporting
confidence: 85%
“…In particular, studies that examined the association of depression and anxiety disorders with subsequent school termination found either that the association does not exist when viewed prospectively (Johnson, Cohen, Dohrenwend, Link, & Brook, 1999) or that, where it exists, it is attributable entirely (Fergusson & Woodward, 2002;Miech, Caspi, Moffitt, Wright, & Silva, 1999) or in large part (McLeod & Kaiser, 2004;Woodward & Fergusson, 2001) to childhood adversities that precede the onset of disorders and are likely to have independent effects on educational attainment. On the other hand, studies examining impulse-control and substance use disorders have found associations with subsequent school termination that remain significant after accounting for childhood adversities.…”
mentioning
confidence: 99%
“…An example is the study by Fergusson and Woodward (2002). They 9 find that the relationship between adolescent depression and subsequent educational underachievement could be fully explained by a range of social, familial and personal factors.…”
Section: Introductionmentioning
confidence: 99%
“…The reports on the timing of abortions were analyzed with regard to consistency over the different reports and validated by means of population estimates. We were able to control for an unusually broad variety of factors, previously reported to be associated with later abortion risk, such as socio-demography, socio-economic and family factors [4,5], early-onset and previous conduct problems, substance use and substance use problems [5,6], educational and job careers [7,8], mental health and personality factors [9,10]. Special analyses addressed the possibility of reverse causality.…”
mentioning
confidence: 99%